2022
DOI: 10.5114/ada.2022.117529
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of circadian profile and blood pressure control in patients with systemic lupus erythematosus without overt heart disease

Abstract: Introduction: Lupus erythematosus (SLE) is an autoimmune disease that causes a significantly increased risk of cardiovascular diseases. This process is underlain by the early and accelerated atherosclerosis. Aim: To assess the diurnal blood pressure profile disturbances in normotensive patients without overt cardiovascular disease and to correlate with early atherosclerotic markers. Material and methods: The study included 32 baseline normotensive women with SLE and 30 healthy control women. Each participant u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Systolic blood pressure level was significantly elevated in SLE group contrasted to the level of the control group. This agreed with several studies which reported increased level of SBP in SLE than normal persons suggesting association between inflammatory markers and elevated SBP in SLE group [7][8][9] . Also, the hemoglobin (Hb) concentration was significantly reduced in SLE group contrasted to the level of the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Systolic blood pressure level was significantly elevated in SLE group contrasted to the level of the control group. This agreed with several studies which reported increased level of SBP in SLE than normal persons suggesting association between inflammatory markers and elevated SBP in SLE group [7][8][9] . Also, the hemoglobin (Hb) concentration was significantly reduced in SLE group contrasted to the level of the control group.…”
Section: Discussionsupporting
confidence: 93%